Mapping the regional sustainable development - Vladimir Sergeevich Tikunov; Dmitriy Anatolievich Tsapuk (European Regional Science Association (ERSA), 1998)
Different opinions about the idea of "sustainable development" (SD) are discussed and the structure of SD indexes is suggested. The last one is based on one of the main methodological statements of the modern geography. It tells, that the basement of the complicated territorial systems or complexes are nature, population, economy. There are distinguished two main types of the original status of the studied regions: - Regions, where the necessity to solve the acute ecological problems force to address to the questions of SD. It means that here it is observed the leading role of ecological factor. More often these are regions of ecological hazards, low developed territories with the raw materials and resources specialization. - Regions where ecological problems are stocked in the tight knot of contradictions with the social-economic and ethno-cultural problems, that means that the "leading" factor hardly could be marked out. It is obvious, that to these two situations must correspond the different orientation of the SD indexes. In first case the priority will be given to the exclusively ecological criterious, in second case - the complex system of indexes will be needed. There is suggested the structure of the system of the SD indexes for territories, which will be the specific framework on composing the model of SD. The maps, or the system of maps or atlas are the more flexible instrument than the system of indexes, because they represent the territorial "reference" and spatial image of the objects and events. Map creation coming from the announced principals must base on the certain indexes, added as the characteristic of SD for the certain region. This makes us to substantiate the certain system of the SD indexes for the regional level. Analysis shows, that in order to reach substantial completeness, it is useful to divide the indexes into 3 groups: - particular indexes of elements and components of the subsystems "nature" (characteristics of environmental conditions and resources), "population" (socio-demographic characteristics of different groups of the population), "economy" (characteristics of different branches); - problematic (structural) indexes, characterizing interlinks between ecological conditions and social-economic conditions; - general system indexes, giving the integrity to the whole set of indexes and characterizing as stability of every system, so as the degree of SD of the territory. Today authors is occupied in realization on the basis of the suggested concept some sheets of the SD atlas of Jaroslavl area (Russia). The concept of the SD atlas of the region is being realized in practice within the geographic ingormation system (GIS) "Terra". "Terra" is worked out on the order of the authorities of Jaroslavl area and now it is the first stage of creation of the integral territorial cadastre of Jaroslavl area as a part of the integral state cadastre of Russia. For today the multi-layer electronic maps of Jaroslavl area are realized within the GIS "Terra" (the basic scale is 1:100,000, for the territories of towns - 1:10,000). Along with that the data base is being created, corresponding to the certain layers of maps (forests, road infrastructure, settlements, administrative districts, building objects, etc.). The concrete working through the possibilities of the atlas creation and testing of the IGS "Terra" are carried out on creations of electronic versions of two maps, which thematic was chosen with account of the present data and theoretical approaches. These are the questions of antropogenic load on environment and general pollution of the territory.
Keywords: 330